Sistema De Información Administrativo Para La Empresa De Bordados Industriales “JUNGLA” Armenia (2016)
The present draft grade, born with the purpose of identify those processes that the company Bordados Industriales “Jungla” Armenia makes in your organization , because it is in a situation of disinformation and little control of commercial operations performed each day however they carry by hand control they fail to accurately know the distribution of resources. It was therefore considered necessary to systematize information by building an administrative system that will identify, manage and integrate business processes of the organization, solving the problem of disinformation and poor control of commercial operations, allowing the company to know precision current status and also acquire the necessary skills to support increase expectations.